Identification of responsive genes and analysis of genes with bacterial-inducible cis-regulatory elements in the promoter regions in Oryza sativa L. - Abbas SAIDI; Zohreh HAJIBARAT; Zahra HAJIBARAT (Acta Agriculturae Slovenica, 2020)
Bacterial blight of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most critical diseases in rice.  In order to study rice responsive genes to bacterial stress, microarray data were retrieved from GEO dataset. To identify the responsive genes to biotic stress (bacteria) bioinformatic tools were employed and the data presented in the forms of heatmap, gene ontology, gene network, and cis-element prediction were used. Almost all responsive genes were down-regulated at around 3 h time point and up-regulated 24 h time point in response to bacterial stress in rice varieties (Oryza sativa subs. japonica ‘IR64’, ‘IRBB5’, ‘IRBB7’ and ‘Y73’). Gene ontology showed that genes are involved in different biological processes including translation and cellular protein metabolic processes. Network analysis showed that genes expressed in response to pathogen infection (Xoo) included protein translation, eukaryotic initiation factors (eIFs), ribosomal proteins, protein ubiquitin, and MAPK genes. The genes expressed in response to bacterial stress can enable plant balance between synthesis and degradation of proteins which in turn allows plants for further growth and development. TATA-box and CAAT box had the highest number of cis elements involved in bacterial stress. These genes can provide novel insights into regulatory mechanisms in biotic stress responses in rice. Identification of bacterial stress response/tolerance genes of rice can assist the molecular breeding of new rice varieties tolerant to bacterial stress.